2003
DOI: 10.1093/intimm/dxg118
|View full text |Cite
|
Sign up to set email alerts
|

The B subunit of Shiga toxin coupled to full-size antigenic protein elicits humoral and cell-mediated immune responses associated with a Th1-dominant polarization

Abstract: A number of studies in animal models and humans have shown that both humoral andcell-mediated immune responses play an important role in the control of viral infection and tumor development. In most cases, vaccination with non-vectorized peptides or proteins induces low antibody responses and fails to elicit specific cytotoxic T lymphocytes (CTL). In order to make vaccination more efficient, we chemically coupled the non-toxic B subunit of Shiga toxin (STxB) to a full-size antigenic model protein, ovalbumin (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 56 publications
0
57
0
Order By: Relevance
“…Both VT1 holotoxin and VTB can deliver antigens for MHC presentation, but how each targets antigens to the cytosol for presentation is unknown (Haicheur et al, 2003;Noakes et al, 1999;Vingert et al, 2006). Our results favour a retrograde ER translocation pathway in verotoxin-sensitive cells but a less efficient endosomal pathway for verotoxin-insensitive antigen presentation remains possible (Falguieres et al, 2001).…”
Section: Discussionmentioning
confidence: 65%
“…Both VT1 holotoxin and VTB can deliver antigens for MHC presentation, but how each targets antigens to the cytosol for presentation is unknown (Haicheur et al, 2003;Noakes et al, 1999;Vingert et al, 2006). Our results favour a retrograde ER translocation pathway in verotoxin-sensitive cells but a less efficient endosomal pathway for verotoxin-insensitive antigen presentation remains possible (Falguieres et al, 2001).…”
Section: Discussionmentioning
confidence: 65%
“…However, successful targeting of antigen to DC has also been associated with antibody induction [67], which may explain previous results regarding the ability of STxB-OVA to increase the amount of OVA-specific IgG2a antibodies in mice [25].…”
Section: Discussionmentioning
confidence: 77%
“…Recently, it was shown that oral immunization with STxB linked to a fragment of the immunogenic rotavirus nonstructural protein (NSP4) protects mice against gastroenteritis mediated by a rotavirus challenge, and this was associated with a strong Th1-mediated response [24]. In a previous study, we showed that STxB efficiently targets exogenous peptides into the MHC class I pathway and induces humoral and cell-mediated immune responses [25]. In the present study, we show that STxB delivers antigen directly to DC in vivo and induces a robust and long-lasting specific CD8 + T cell response detected directly ex vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage of this system is that STxB can be manipulated without altering the affinity and specificity of its interaction with Gb 3 on target cells (25). Moreover, STxB is a little immunogenic protein with MHC dependence (26).…”
Section: Introductionmentioning
confidence: 99%